Chiral Hydrogel Accelerates Re‐Epithelization in Chronic Wounds via Mechanoregulation. Issue 21 (9th September 2022) - Zhu, Hanting; Xing, Chao; Dou, Xiaoqiu; Zhao, Yu; Peng, Yinbo; Feng, Chuanliang; Fang, Yong
Abstract: Chronic wounds, such as diabetic foot ulcers (DFU), are a serious clinical problem. It is a challenge for the conventional wound dressings to achieve the desirable therapeutic efficacy due to the lack of biomimetic structural environment for rapid re‐epithelization. Inspired by the naturally existing chiral structures in skin, a novel amino acid‐based chiral hydrogel dressing is developed, consisting of left‐handed or right‐handed helical fibers self‐assembled by l/d –phenylalanine derivatives. Compared to the levorotatory chiral hydrogel (LH), the dextral chiral hydrogel (DH) shows the ability to enhance cell adhesion, proliferation, and migration, and strongly promotes diabetic wound healing and re‐epithelialization with a drug‐free mode. Interestingly, the dextral chiral hydrogel is able to actively increase adsorption of type I collagen and promote proliferation and migration of keratinocyte in an integrin and YAP‐mediated manner. This study not only provides a novel strategy for treatment of chronic wounds by utilizing dextral chiral hydrogel dressings, but also unveils the molecular mechanism for effect of dextral chiral structures on the promoted proliferation of keratinocyte. Abstract : Extracellular matrix biomimetic hydrogels based on chiral constructs regulate the regeneration of diabetic wound epidermal cells. The extral chiral structure provides induction of Type I collagen tethering, which causes significant alterations in mechanoregulation signaling pathways, thus promoting the proliferation and migration of cells. Such a biocompatible material opens the door to a better understanding of the biomedical applications of chiral structures.